Physiologically relevant factors influence tau phosphorylation by leucine‐rich repeat kinase 2. Issue 10 (30th June 2015) - Hamm, Matthew; Bailey, Rachel; Shaw, Gerry; Yen, Shu‐Hui; Lewis, Jada; Giasson, Benoit I.
Abstract : Hyperphosphorylation and aggregation of tau are observed in multiple neurodegenerative diseases termed tauopathies . Tau has also been implicated in the pathogenesis of Parkinson's disease (PD) and parkinsonisms. Some PD patients with mutations in the leucine‐rich repeat kinase 2 ( LRRK2 ) gene exhibit tau pathology. Mutations in LRRK2 are a major risk factor for PD, but LRRK2 protein function remains unclear. The most common mutation, G2019S, is located in the kinase domain of LRRK2 and enhances kinase activity in vitro. This suggests that the kinase activity of LRRK2 may underlie its cellular toxicity. Recently, in vitro studies have suggested a direct interaction between tubulin‐bound tau and LRRK2 that results in tau phosphorylation at one identified site. Here we present data suggesting that microtubules (MTs) enhance LRRK2‐mediated tau phosphorylation at three different epitopes. We also explore the effect of divalent cations as catalytic cofactors for G2019S LRRK2‐mediated tau phosphorylation and show that manganese does not support kinase activity but inhibits the efficient ability of magnesium to catalyze LRRK2‐mediated phosphorylation of tau. These results suggest that cofactors such as MTs and cations in the cellular milieu have an important impact on LRRK2‐tau interactions and resultant tau phosphorylation. © 2015 Wiley Periodicals, Inc. Abstract : MTs promote LRRK2‐mediated phosphorylation of tau at T149, T153, and T205. Tau hyperphosphorylation is associated with aggregation and formation of disease‐pertinent tau species. Thus LRRK2‐mediated tau phosphorylation may represent an avenue of disease pathogenesis in LRRK2‐related PD.